BAHASA TABU DALAM MASYARAKAT GAYO DI KABUPATEN ACEH TENGAH - Rahmawati; Alfi Syahrin; Ezmar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Taboo language is a linguistic phenomenon reflecting the close relationship between language, culture, and social norms within a society. This study aims to describe the forms and classifications of taboo language and to explain the social contexts of its use among the Gayo people in Central Aceh Regency. A descriptive qualitative approach was employed. Data were gathered through listening, participatory observation, recording, and note-taking involving three native Gayo speakers from the Kute Panang, Ketol, and Kebayakan districts. Data analysis involved data reduction, data presentation, and conclusion drawing. The results identified 39 instances of taboo language, classified into six categories: taboos regarding personal names, animal names, body parts, disease names, specific words, and profanity. The use of taboo language is influenced by fear, politeness, comfort, and religious teachings. Furthermore, its usage is heavily influenced by social contexts, including age, kinship ties, social status, location, and the communicative situation. The Gayo community also employs euphemisms—a form of linguistic softening—to avoid uttering words considered taboo. The study demonstrates that taboo language continues to function as a mechanism for upholding social norms, linguistic politeness, and the cultural identity of the Gayo people, even though it is undergoing shifts due to social change and the evolution of the times.